ترجمة الصّور البيانيّة في النّصوص الماليّة من الانكليزيّة إلى العربيّة والفرنسيّة مقالات مجلة "التّمويل والتنميّة" -إصدار صندوق النّقد الدّولي -أنموذجا : Translation of Figures of Speech in Financial Texts From English into Arabic and French Case Study: Articles of “Finance & Development” Magazine, Published by the International Monetary Fund (IMF) - لعيمش ليلى (Maalim, 2022)
Figures of speech are present in all languages and cultures. They represent an important field of study for rhetoricians and translators. Also, figures of speech are not limited to prose and poetry; they have become a distinctive feature of some specialised languages like the language of economics and finance. In the "Finance & Development" magazine (F&D), published by the IMF, researchers, experts, and economists tend to use figures of speech in their articles and reports to grab the reader’s attention. Thus, the aim of this work is to explain the different types of figures of speech (in Arabic, English, and French), and to analyse some translated examples, taken from some issues of the abovementioned magazine, in order to determine the techniques of translation used to ensure a faithful transfer of those figures, according to the specialised contexts in which they occur.